Polyculturalism and Attitudes Toward the Continuing Presence of Former Colonizers in Four Postcolonial Asian Societies - Bernardo, Allan B. I.; Salanga, Maria Guadalupe C.; Tjipto, Susana; Hutapea, Bonar; Khan, Aqeel; Yeung, Susanna S. (Frontiers in Psychology, 2019)
Polyculturalism is the lay belief that cultures are dynamically interconnected and mutually influencing each other historically and in contemporary times. Belief in polyculturalism is associated with various positive intergroup outcomes in intercultural social contexts, but it has never been studied in relation to intergroup attitudes in postcolonial societies. Two studies with participants (total N = 1,126) from four postcolonial Asian societies explore whether polyculturalism will also be associated with positive attitudes towards the continuing presence of former colonizers. The historical colonial experience may be socially represented positively or negatively in different societies, and in this context, the studies inquire into whether current attitudes towards former colonizers are positively associated with the belief in polyculturalism. In two studies, (after controlling for belief in multiculturalism, genetic and social constructivist lay theories of race, national identity) polyculturalism was positively associated with favorable attitudes towards continuing presence of former colonizers in Hong Kong, Macau, and Jakarta, but not in Johor Bahru, Malaysia and Wonosobo, Indonesia. The positive association with polyculturalism was found only in the three societies with a high degree of intercultural contact, where the core beliefs of polyculturalism may be more meaningful. The results are discussed in terms of how intergroup relations between former colonizers and colonized peoples are forms of between-society intercultural contact that is also influenced by intergroup lay theories.